Patterns of velocity in competitive breaststroke swimming - Craig, A. B.; Boomer, W. L.; Skehan, P. L. (Swimming Science V, 1988)
In competitive swimming, increased velocity is associated with an increase in stroke rate and a decrease in the distance traveled per stroke cycle (Craig, Boomer, & Gibbons, 1979; Craig & Pendergast, 1979; Craig, Skehan, Pawelczyk, & Boomer, 1985; Pai, Hay, & Wilson, 1984). The velocity, which is the product of stroke rate and distance per stroke, can increase only if the increase of the stroke rate is proportionally greater than the decrement of the distance per stroke. In the breaststroke the decrease of the distance per stroke with increasing stroke rates is greater than in other stroke patterns (Craig & Pendergast, 1979). It has also been reported that the fluctuations in velocity are greater in the breaststroke than in the other competitive strokes (Craig & Pendergast, 1979). Previous documentation of the variations in velocity and the temporal relations within this competitive stroke pattern have been limited to one or two individual swimmers (Bober & Czabanski, 1975; Kent & Atha, 1975; Schleihauf, 1979). Publications were not found that indicated the temporal and velocity changes during the stroke cycle for a range of stroke rates.